Managing Sciatica and Radicular Pain in Primary Care Practice - Laroche, Francoise; Perrot, Serge; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
Low back pain is described as a very common condition that tends to affect about 70% of the population at some point in time with varying degrees of symptom severity. Although definitions vary, sciatic pain is generally defined as back-related pain radiating to the leg (normally below the knee and into the foot and toes) and is one of the commonest variations of low back pain. Patients with sciatica typically experience a more persistent and severe type of pain, a less favorable outcome, consume more healthcare resources and have more prolonged disability and absence from work than those with low back pain alone. Managing Sciatica and Radiculopathies in Primary Care Practice provides a comprehensive, up-to-date overview of the subject and key information for primary care practitioners about low back pain in patients, including definitions and causes, current management approaches, diagnostic and treatment algorithms, as well as clinical practice guidelines.
What is sciatica and radicular pain? -- What are the causes of sciatica and radicular pain? -- How are sciatica and spinal radicular pain classified? -- How are the radiculopathies diagnosed? -- What guidelines are available for sciatica and radicular pain? -- Physical and psychological treatments -- What are the options for the surgical treatment of radiculopathy? -- Pharmacological treatment options available for radicular pain.
Keywords: Medicine; Orthopedics; Orthopedic surgery; Pain Medicine; Medicine & Public Health; Orthopedics; Pain Medicine; Pharmacotherapy; Surgical Orthopedics